Potensi Penggunaan Pembangkit Listrik Tenaga Sampah (PLTSa) Sebagai Energi Terbarukan Guna Mengurangi Permasalahan Lingkungan - Inggritiya, Sefti Eka; ., Yusuardi; ., Sudarti (CV. ITTC INDONESIA, 2023)
Waste is one of the factors causing various environmental problems, especially in Indonesia. Waste piles up everywhere due to the lack of public awareness of good waste management. Over time, the accumulation of waste can have adverse effects, ranging from health problems to environmental damage to the economy. This research aims to describe environmental problems, especially waste or garbage, and whether waste power plants are a solution to electricity needs or environmental problems. This research uses a literature study research method or literature review. The existence of this PLTSa development can reduce environmental problems, more precisely waste in Indonesia.